Citizenship and nationhood in France and Germany - Brubaker, Rogers, 1956- (Harvard University Press, 1992)
The difference between French and German definitions of citizenship is instructive - and, for millions of immigrants from North Africa, Turkey, and Eastern Europe, decisive. Brubaker explores this difference - between the territorial basis of the French citizenry and the German emphasis on blood descent - and shows how it translates into rights and restrictions for millions of would-be French and German citizens. Why French citizenship is territorially inclusive, and German citizenship ethnically exclusive, becomes clear in Brubaker's historical account of distinctive French and German paths to nation-statehood. Two fundamental legal principles of national citizenship emerge from this analysis, leading Brubaker to broad and original observations on the constitution of the modern state.